PERAN RADIOGRAFI DALAM IDENTIFIKASI KASUS FORENSIK ODONTOLOGI - Rizki Tanjung (Jurnal Kedokteran Gigi Terpadu, 2021)
Background: Radiography is an important part of forensic odontology because it is a simple, economical, and non-invasive method in identification, especially for identifying corpses through proper comparison between antemortem and post-mortem radiographs. Radiographs can also be taken to determine the victim’s age and even assist in assessing gender and ethnic group. Dental radiographic examination can be used as a reference because it has minimal potential for error compared to an odontogram. Objective: To describe the basic principles of dental radiology that play a role in forensic odontology. Discussion: Dental radiographs can provide accurate information as comparative data from antemortem data. The correct technique will produce an optimal image to be interpreted as comparative data through the anatomical shape of the teeth, periapical abnormalities, fillings, caries outlines, the position of impacted teeth, and others. Information obtained from panoramic radiographs helps estimate age and sex. Age estimation was carried out by observing the eruption stage of the teeth. In contrast, gender estimation was carried out by assessing the landmarks of maxillofacial anatomical structures. Conclusion: Radiography is needed in forensic odontology as an important component to support the identification process.